Revisiting “Steady-State” Monotonic and Cyclic Deformation: Emphasizing the Quasi-Stationary State of Deformation - Mughrabi, Hael (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2020)
High-temperature creep, cyclic deformation in saturation, and a number of technologically important processes are typical examples of the so-called “steady-state” deformation. These cases are usually defined in terms of the constancy of the mechanical parameters. Moreover, it is usually assumed that the deformation-induced microstructure undergoes no further changes. However, clear evidence shows that non-negligible microstructural changes continue to occur in the so-defined steady-state high-temperature creep and in cyclic saturation. It can be shown that the so-called “steady-state” deformation is actually a quasi-stationary deformation which is characterized by the initial development of a “mechanical steady state”, which is followed with a delay by a “microstructural steady state.” Only the latter can then be considered as a true steady state. A deeper analysis reveals a persistent slight increase of the dislocation density, with geometrically necessary dislocations in the cell walls/subgrain boundaries, causing the latter to transform gradually into sharper boundaries with higher misorientations. These findings, based on a detailed analysis of a wide range of experimental studies, are found to be almost identical for both high-temperature creep and cyclic deformation in saturation and are hence considered as characteristic of quasi-stationary deformation. The analysis clarifies, as a by-product, specific effects which arise from the increasing heterogeneity of the dislocation pattern (patterning). Thus, a marked decrease of the arrangement factor “alpha” in the Taylor flow stress is noted, as patterning proceeds, in agreement with predictions of the so-called composite model. Since this effect is compensated partially by the increase of the dislocation density, the flow stress remains rather insensitive to subtle microstructural changes. Based on these facts, the need for revision of current flow-stress formulations in future dislocation modeling is emphasized.
CRIS-Team Scopus Importer:2020-02-14